Long-term outcomes stratified by age in patients with a mechanical versus biological mitral valve replacement - Veres, Gábor; Benke, Kálmán; Stengl, Roland; Weber, Petra; Marina, Ereva; Szabó, Gábor; Karck, Matthias (Journal of cardiovascular development and disease, 2022)
Objectives: Balancing anticoagulation and reoperation risks determines prostheses choice (mechanical/biological) for mitral valve replacement. We aimed to re-evaluate the outcomes after biological versus mechanical mitral valve replacement. Methods: We compared long-term benefits and risks of mechanical and biological prostheses in 2056 patients (52% men, 48% women; 65.4 ± 12.1 years) who underwent mitral valve replacements between 1993-2017, in a retrospective single-centre study. Data sources included prospective institutional database, social registry, general practitioner data and follow-up questionnaire. Patients were stratified by age: < = 39 y (n = 82), 40-49 y (n = 164), 50-59 y (n = 335), 60-69 y (n = 593), 70-79 y (n = 743) and > = 80 y (n = 139). Long-term outcomes (mortality, reoperations, bleeding) were analysed. Results: Altogether, 1308 mechanical (53% men, 47% women; 61.5 ± 11.7 years) and 748 biological (50% men, 50% women; 72.3 ± 9.6 years) valves were implanted. The reason for valve replacement was stenosis in 162, insufficiency in 823 and combined in 323 cases for mechanical, while it was 46, 567 and 135 for biological valves, respectively. Overall cumulative survival was higher with mechanical prosthesis (mean: 139 ± 4 vs. 102 ± 5 months, 10 y: 55% vs. 33%, p < 0.0001). Subgroup analysis revealed higher survival among patients receiving mechanical prosthesis up to 60 years (< = 39 y p = 0.047, 40-49 y p < 0.0001, 50-59 y p = 0.001). In patients 60-69 years, overall survival did not differ; however, in survivors beyond 8 years, mechanical prosthesis showed improved survival (p = 0.014). While between 70-79 years survival was nearly identical, for above 80 years, patients had a higher survival with biological prosthesis (p = 0.014). Conclusion: The present data demonstrated a higher survival of mechanical prosthesis in a wide range of patients after mitral valve replacement.